Hexahydro-1,2,3-triazine Derivatives: Synthesis, Antimicrobial Evaluation, Antibiofilm Activity and Study of Molecular Docking Against Glucosamine-6-Phosphate - Nabel Bunyan Ayrim; Fadhel Rukhis Hafedh; Yasir Mohamed Kadhim; Abduljabbar Sabah Hussein; Ahmed Mutanabbi Abdula; Ghosoun Lafta Mohsen; Mohammed Mahdi Sami (Universitas Gadjah Mada, 2024)
The N,N',N''-trisubstituted hexahydro-1,3,5-triazine derivatives (3a–g) had been created and identified through infrared, nuclear magnetic resonance, and mass spectrometry according to their symmetric basic structure. Three molecules of diverse aromatic amines and three molecules of formaldehyde were assembled in a